2013
DOI: 10.1159/000351130
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Body Composition and Glomerular Filtration Rate Estimates in the General Population

Abstract: Background: Differences in body composition may lead to imprecision in estimates of glomerular filtration rate (eGFR) derived from serum creatinine. Our aims were to examine the relationship between eGFR and anthropometric and body composition measures and handgrip strength. Methods: We analyzed data from a cross-sectional study comprising 1,630 randomly selected community-dwelling adults. The Modification of Diet in Renal Disease (MDRD) and Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
0
9
1
Order By: Relevance
“…We found that a high BFP and elevated serum hsCRP levels were both associated with a reduced eGFR in our subjects. Contrary to previous studies showing that obesity is associated with an increased risk of CKD and its progression, [ 3 , 16 , 25 , 26 ] our results suggest that a high BFP in the setting of acute inflammation (represented with elevated hsCRP level) might reduce the risk of CKD, especially in overweight or obese patients.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We found that a high BFP and elevated serum hsCRP levels were both associated with a reduced eGFR in our subjects. Contrary to previous studies showing that obesity is associated with an increased risk of CKD and its progression, [ 3 , 16 , 25 , 26 ] our results suggest that a high BFP in the setting of acute inflammation (represented with elevated hsCRP level) might reduce the risk of CKD, especially in overweight or obese patients.…”
Section: Discussioncontrasting
confidence: 99%
“…Different body compositions such as the ratio between and distribution of lean mass and adipose tissue compartments may be associated with metabolic risks. [ 14 16 ] However, the BMI does not differentiate lean mass from fat mass. [ 17 ] To circumvent this limitation, other measures for estimating adiposity have been proposed, including body fat percentage (BFP) or waist circumference (WC).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic kidney diseases in patients with diabetes lead to end-stage renal failure, which is closely associated with the onset of cardiovascular diseases and all-cause deaths [10, 11]. Urinary albumin level, urinary protein level, and estimated glomerular filtration rate (eGFR) are clinically evaluated as the markers of renal function [12, 13]. Previous studies have demonstrated that urinary albumin level [14–16] or decreased eGFR [17, 18] is related to insulin resistance, inflammation, oxidative stress, and vascular endothelial dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Creatinine, is actively secreted by the proximal tubule, and is related to muscle mass, age, sex, ethnicity and dietary factors [1,3]. Creatinine concentrations can be higher in individuals with an increased muscle mass, independent of kidney function, leading to an underestimation of eGFR [4]. Studies in adults suggest that eGFR based on creatinine concentrations can be improved if lean mass percentage could be incorporated in the formula [4].…”
Section: Introductionmentioning
confidence: 99%